La prostitution à Beyrouth sous le mandat français (1920-1943) - Nessim Znaien (Genre & Histoire)
This article uses administrative archives and medical sources to examine the phenomenon of prostitution in Beyrouth during the French Mandate between 1923 and 1946. It offers a comparative perspective of public health policies toward prostitution in Beyrouth, North Africa and Indochina. The aim of theses policies was to control rather than to prohibit public prostitution, using brothels, for example, much as the French did elsewhere in mainland France or in the French Empire. The French administration had two objectives : on the one hand, it sought to generate revenue thanks to taxation on this business ; on the other hand, it kept a close eye on prostitutes providing them with medical assistance in order to avoid venereal diseases among soldiers. This administrative management rendered prostitution visible in public areas and became the focus of certain religious and nationalist conflicts.